A Critique of Abdul Mustaqim’s Concept of Tafsir Maqāṣidī: Methodological Simplification and Its Implications for Online Qur’anic Interpretation - Lufaefi Lufaefi; Isyroqotun Nashoiha; Zulfadhilah Ismail; Ihwanul Muadib; Nia Ariyani; Waesul Kurni (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
This study critically examined Abdul Mustaqim’s concept of tafsir maqāṣidī and its implications for contemporary online Qur’anic interpretation. Abdul Mustaqim’s maqāṣidī interpretation offers important contributions to contemporary tafsir studies by emphasizing moderation (wasathiyah), contextual understanding, public benefit (maṣlaḥah), and humanitarian values as the main orientation of interpreting the Qur’an. This approach successfully bridges the tension between rigid textualism and liberal relativism, making Qur’anic interpretation more socially relevant and responsive to modern issues such as tolerance, justice, and religious harmony. This research used a qualitative library research method with descriptive-analytical and critical-methodological approaches. The findings showed that although maqāṣidī interpretation strengthens socially relevant Islamic discourse, its methodological simplification risks reducing the complexity of Qur’anic interpretation and increasing ideological subjectivity in digital tafsir practices.